Association between circulating CD34-positive cell count and height loss among older men - Shimizu, Yuji; Kawashiri, Shin-Ya; Nobusue, Kenichi; Nonaka, Fumiaki; Tamai, Mami; Honda, Yukiko; Yamanashi, Hirotomo; Nakamichi, Seiko; Kiyama, Masahiko; Hayashida, Naomi; Nagata, Yasuhiro; Maeda, Takahiro (Scientific reports, 2022)
Height loss starting in middle age is reportedly significantly associated with death due to cardiovascular disease. Impaired blood flow is the main pathology in cardiovascular disease. Hematopoietic stem cells such as CD34-positive cells play an important role in maintaining the microcirculation and preventing impaired blood flow by activating endothelial repair and angiogenesis. Therefore, circulating CD34-positive cell count could be associated with height loss. To clarify the association between circulating CD34-positive cell count and height loss, we conducted a follow-up study of 363 Japanese men aged 60–69 years over 2 years. Height loss was defined as being in the highest quartile of height decrease per year. Independent of known cardiovascular risk factors, circulating CD34-positive cell count was significantly inversely associated with height loss. The fully adjusted odds ratio (OR) and 95% confidence interval (CI) of height loss for circulating CD34-positive cell count (logarithmic values) was 0.49 (0.32, 0.74). This study suggests that a lower capacity to maintain the microcirculation due to a fewer CD34-positive cells might affect height loss.